2010
DOI: 10.1017/s1047951110000697
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of low-density lipoprotein oxidation, paraoxonase activity, and arterial distensibility in epileptic children who were treated with anti-epileptic drugs

Abstract: Anti-epileptic drugs may induce atherogenesis by affecting the thyroid hormones. According to the current data, the effects of thyroid hormones on vascular system may be independent of other biochemical markers. Epileptic patients using anti-epileptic drugs must be followed closely for arterial stiffness, and also for the development and progression of atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 39 publications
0
20
0
1
Order By: Relevance
“…This is plausible when it is considered that arterial stiffness is influenced by elastic fiber degeneration, increased collagen and hypertrophy in vascular smooth muscle layers, all of which are related to oxidative stress 10) ; however, data are limited and controversial regarding the association among PON1 and AS. Yang et al reported an association between PON1 levels, carotid intima thickness and cf-PWV, whereas Yildiz et al found no association in patients with epilepsy 10,11) . Several limitations of our study should be noted.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This is plausible when it is considered that arterial stiffness is influenced by elastic fiber degeneration, increased collagen and hypertrophy in vascular smooth muscle layers, all of which are related to oxidative stress 10) ; however, data are limited and controversial regarding the association among PON1 and AS. Yang et al reported an association between PON1 levels, carotid intima thickness and cf-PWV, whereas Yildiz et al found no association in patients with epilepsy 10,11) . Several limitations of our study should be noted.…”
Section: Discussionmentioning
confidence: 98%
“…In one study, low PON1 levels were shown to be an independent predictor of carotid-femoral PWV (cf-PWV) in hypertensive patients 10) . In contrast, Yildiz et al reported no association between PON1 levels and AS 11) . Thus, in this cross-sectional study we aimed to investigate the association between PON1 and AS in RT patients.…”
Section: Introductionmentioning
confidence: 90%
“…34,35 According to current data, there are a few studies in the literature in which connection of PON1 with PWV were evaluated. 18,39,40 Recently, we investigated the mechanism of the effect of valproic acid, carbamazepine, and valproic acid+carbamazepine by determining serum levels of oxidized low-density lipoprotein, apolipoprotein A1, homocysteine, folic acid, vitamin B12, PON1, total antioxidant capacity, malondialdehyde, nitric oxide and thyroid hormones in pediatric epileptic patients. 18 Besides the level of apolipoprotein A1, the activity of PON1 remained unaffected in pediatric patients who used antiepileptic drugs.…”
Section: Paraoxonasementioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][18][19][20] In fact, the most important factor contributing to increased aortic PWV in humans is age because it causes increased arterial stiffness due to decreased elastin fiber, increased collagenous material and loss of arterial elasticity. [21][22][23] Increased medial calcification and endothelial dysfunction are also characteristics of arterial aging.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Although there are several methods currently available to assess arterial stiffness, researchers and clinicians still face problems in selecting the best methodology for their specific use. This paper summeries the advantages and disadvantages of pulse wave velocity (PWV) and augmentation index (AI) in the assessment of arterial stiffness.…”
Section: Assessment Of Arterial Stiffness With Pulse Wave Velocity Ormentioning
confidence: 99%